The New Plastic Flow Machining Process for Producing Thin Sheets - Viet Q. Vu; Yan Beygelzimer; Roman Kulagin; Laszlo S. Toth (Advances in Materials Science and Engineering)
A new severe plastic deformation (SPD) process called plastic flow machining (PFM) was recently proposed to produce thin sheets with gradient structures. In the present paper, the role of the die geometry is investigated by studying the effects of the produced sheet thickness (h) on the material properties of commercial pure Aluminum (Al1050) processed by PFM. The obtained experimental results show that an increase of h in the range of 0.65 to 1.5 mm improved the formation efficiency of the sheet. Microstructures of the produced sheets show gradient structures with an average grain size varying from 0.8 to 3.81 µm across the sheet thickness. Both experiments and finite element (FE) simulations document that the degree of the gradient in the microstructure became more significant when h was increased. Sheets produced by PFM exhibited a better strength-ductility balance than sheets obtained in other SPD processes. Tensile strength of 160–175 MPa and total ductility of 18–25% were obtained for the processed samples after PFM. A rise of h from 0.65 to 1.5 mm lowered the strength but enhanced the ductility of the produced sheet, which is due to the coarser microstructure at larger values of h.